Pemasaran Efektif di Era Digital: Membuka Toko Online di Platform Marketplace Indonesia - Athaya, Athaya; Wahyudin, Wahyudin (Jurnal PKM Manajemen Bisnis, 2024)
Digital marketing has become an important element in a company's marketing strategy in the current digital era. This also applies to small and medium enterprises (SMEs). One of the popular digital marketing platforms in Indonesia is the marketplace. Marketplaces offer various benefits for SMEs, such as ease of managing online stores, access to a wide market, and relatively affordable costs. This community service activity aims to increase the knowledge and skills of SMEs in opening and managing online stores on the Indonesian marketplace platform. This activity is carried out using training and mentoring methods. This community service activity was carried out in Tangerang City, Banten for Batu Ceper Clothing SMEs. The results of the activity show that participants have acquired adequate knowledge and skills in opening and managing an online shop on the Indonesian marketplace platform.